2014
DOI: 10.1016/j.stemcr.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Inflammation Contributes to Brain Overgrowth and Autism-Associated Behaviors through Altered Redox Signaling in Stem and Progenitor Cells

Abstract: SummaryA period of mild brain overgrowth with an unknown etiology has been identified as one of the most common phenotypes in autism. Here, we test the hypothesis that maternal inflammation during critical periods of embryonic development can cause brain overgrowth and autism-associated behaviors as a result of altered neural stem cell function. Pregnant mice treated with low-dose lipopolysaccharide at embryonic day 9 had offspring with brain overgrowth, with a more pronounced effect in PTEN heterozygotes. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 34 publications
(41 reference statements)
2
74
0
1
Order By: Relevance
“…Several differences in white matter micro-structure may yield this combination of diffusion values, including increased myelination, increased axonal density, smaller axonal calibers, and/or increased extra-cellular matrix density (Mori and Zhang 2006). Numerous postmortem (Courchesne and Pierce 2005; Courchesne, Mouton, et al 2011; Santos et al 2011; Stoner et al 2014), genetic (Pinto et al 2010; Chow et al 2012; Bernier et al 2014; Sugathan et al 2014; Pramparo et al 2015), animal model (Fang et al 2014; Le Belle et al 2014; Orosco et al 2014; Sabers et al 2014), and cellular (Marchetto et al 2016; Packer 2016) studies suggest that, in many cases, autism is associated with a prenatal excess of neural proliferation, which would predict an excess of corresponding axons. While postmortem studies with toddlers have not examined axonal characteristics or reported axon numbers in the white matter of toddlers with autism, adults with autism do exhibit an abnormally large number of smaller caliber axons in frontal lobe areas (Zikopoulos and Barbas 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several differences in white matter micro-structure may yield this combination of diffusion values, including increased myelination, increased axonal density, smaller axonal calibers, and/or increased extra-cellular matrix density (Mori and Zhang 2006). Numerous postmortem (Courchesne and Pierce 2005; Courchesne, Mouton, et al 2011; Santos et al 2011; Stoner et al 2014), genetic (Pinto et al 2010; Chow et al 2012; Bernier et al 2014; Sugathan et al 2014; Pramparo et al 2015), animal model (Fang et al 2014; Le Belle et al 2014; Orosco et al 2014; Sabers et al 2014), and cellular (Marchetto et al 2016; Packer 2016) studies suggest that, in many cases, autism is associated with a prenatal excess of neural proliferation, which would predict an excess of corresponding axons. While postmortem studies with toddlers have not examined axonal characteristics or reported axon numbers in the white matter of toddlers with autism, adults with autism do exhibit an abnormally large number of smaller caliber axons in frontal lobe areas (Zikopoulos and Barbas 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal inflammation during critical periods of embryonic development can cause brain overgrowth and autism-associated behaviors as a result of altered neural stem cell function [55]. ROS at nontoxic levels can increase stem cell self-renewal and neurogenesis through the reversible inactivation of the tumor suppressor gene PTEN protein and the subsequent enhancement of the PI3K pathway [56].…”
Section: Microglial Activation In Autismmentioning
confidence: 99%
“…It has not yet been clarified whether the increase in microglia plays a role in stimulating progenitor proliferation [58] or in the phagocytic pruning of cells produced in excess following maternal inflammatory response exposure [17]. However, these murine models of maternal inflammation support the concept that prenatal neuroinflammatory dysregulation in neural stem cell redox signaling can act in concert with underlying genetic susceptibilities to affect the cellular responses to environmentally altered cellular levels of ROS [55]. …”
Section: Microglial Activation In Autismmentioning
confidence: 99%
“…Postmortem data from ASD children, genetic findings (e.g., CHD8, PTEN, EIF4A, WDFY3, KCTD13-CUL3-RhoA) (3038) and ASD animal models (32, 39, 40) point to disruption of cell cycle in fetal development, excess neuron proliferation and brain overgrowth and call into question the anatomical under-connectivity hypothesis. For instance, in young ASD children with heavier-than-normal brain weight, prefrontal cortex has a 67% excess of neurons (41).…”
Section: Introductionmentioning
confidence: 99%